Upaya Mempertahankan Sikap Patriotisme dan Nasionalisme Melalui Pendidikan Kewarganegaraan Untuk Generasi Milenial Dalam Revolusi 4.0 - Mario Ika Putra; Aulia Rachman Heryawan; Muhammad Rifqi Rukmana; Supriyono Supriyono (Jurnal Ilmiah Wahana Pendidikan, 2023)
The influence of the use of social media has reduced the attitude of patriotism and nationalism among the current millennial generation. There are efforts that can be made to reduce these negative impacts. This study aims to describe the efforts that can be made to maintain an attitude of patriotism and nationalism that focuses on the millennial generation in the 4.0 revolution. This research uses a descriptive qualitative approach with the method of literature study from various sources that are relevant to this research. Efforts to maintain an attitude of patriotism and nationalism are needed by the millennial generation in the 4.0 revolution. The values of patriotism and nationalism contained in Pancasila need to be redefined to adapt to conditions in the digital era.